Remnant–to–LDL cholesterol discordance as a predictor of thromboembolic events in anticoagulated patients with atrial fibrillation: a report from the prospective Murcia AF project III (MAFP-III) cohort study - Eva Soler-Espejo; Yang Chen; José Miguel Rivera-Caravaca; María Pilar Ramos-Bratos; Raquel López-Gálvez; Francisco Marín; Vanessa Roldán; Gregory Y.H. Lip (Cardiovascular Diabetology)
Abstract Background Remnant cholesterol (RC) has emerged as an independent contributor to residual cardiovascular risk, beyond low-density lipoprotein cholesterol (LDL-C). As atrial fibrillation (AF) is a common arrhythmia associated with increased thromboembolic risk even despite anticoagulation, we assessed the prognostic value of RC in AF, with a particular focus on its association with LDL-C discordance. Methods In this prospective cohort study, AF outpatients initiating oral anticoagulation between January 2016 and November 2021 were enrolled. Baseline LDL-C and RC levels were measured, and patients were stratified into four groups based on these values. The primary outcome was a composite of thromboembolic events; secondary outcomes included major adverse cardiovascular events (MACE), cardiovascular death, and all-cause death. Associations between RC levels and clinical outcomes across LDL-C strata were assessed using multivariable Cox proportional hazards models and as a continuous variable using restricted cubic spline (RCS) analyses. Results Among 1,694 patients (52.5% female; median age 76 years (IQR 69–82); mean follow-up: 1.86 years, SD 0.4 years), 5.7% (97) experienced incident thromboembolic events. In the low LDL-C group, RCS analysis showed a significant linear association between RC levels and thromboembolic risk (p-overall = 0.044). High RC levels were independently associated with an increased risk of thromboembolic events compared to the low RC subgroup (aHR 1.82; 95% CI, 1.03–3.23; p = 0.039), but this was nonsignificant in the high LDL-C group. For secondary outcomes, higher RC levels were not significantly associated with increased adverse event risk in either LDL-C group. Conclusion Despite low LDL-C levels in AF patients, elevated RC levels were still independently associated with a higher thromboembolic risk, suggesting discordance between RC and LDL-C in risk stratification among patients with AF. Graphical abstract